Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1136/jmedgenet-2011-100552
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation inCC2D2A-related Joubert syndrome reveals an association with ventriculomegaly and seizures

Abstract: CC2D2A testing should be prioritised in patients with JS and ventriculomegaly and/or seizures. Patients with CC2D2A-related JS should be monitored for hydrocephalus and seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 48 publications
(37 reference statements)
2
71
1
2
Order By: Relevance
“…A higher prevalence of ventriculomegaly has been reported in patients with CC2D2A -related JS compared with subjects without CC2D2A pathogenic variants 30. In our cohort, however, ventriculomegaly was associated with pathogenic variants in several genes.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…A higher prevalence of ventriculomegaly has been reported in patients with CC2D2A -related JS compared with subjects without CC2D2A pathogenic variants 30. In our cohort, however, ventriculomegaly was associated with pathogenic variants in several genes.…”
Section: Discussioncontrasting
confidence: 71%
“…In 13 patients with JS, we found a convex protuberance of the ventral contour of the midbrain; in four patients, a similar protuberance was seen at the dorsal contour of the lower medulla. These findings, not described in other disorders, were previously reported in single patients with JS 14 29 30. These protuberances are isointense to grey matter and have a nodular appearance.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…2 It is estimated that known genes overall account for about half of cases, suggesting further genetic heterogeneity; moreover, genotype-phenotype correlates have been clearly established only for few JSRD-causative genes. [5][6][7][8][9] In 2009, Jacoby et al 10 identified INPP5E mutations in a family with MORM syndrome, a rare autosomal recessive condition related to Bardet-Biedl syndrome. In the same year, we identified homozygous INPP5E mutations in seven consanguineous families genetically linked to the first JSRD locus (JBTS1) on 9q34.…”
Section: Introductionmentioning
confidence: 99%
“…The novel mutations c.4559A>G(p.Asn1520Ser) and c.4702T>C(p.Tyr1568His) are predicted to be damaging (by SIFT, Polyphen-2 and Mutation Taster) and neither variant has been reported in the Exome Variant Server (EVS; NHLBI GO Exome Sequencing Project), dbSNP135 or 1000 Genome datasets. These five CC2D2A mutations cluster in either the C2 domain (amino acids 1062–1174) or the C-terminal part of the protein, as do most missenses that cause JBTS 18. Segregation analysis revealed that all the affected individuals, but none of their unaffected relatives, were compound heterozygous for the mutations (see online supplementary figure S1).…”
mentioning
confidence: 99%